Gestión integral del agua en la microcuenca Chuquiribamba-Chantaco - Sivisaca Caraguay, Luis Floresmilo (2012)
This research was carried out in the Chuquiribamba-Chantaco watershed, adapting the methodological water guide inventory, given by the National Water Forum, to inventory water for the Chantaco Chuquiribamba watershed , in terms of quantity and quality. The rationality of farmers was studied on water management aspects and the use in cropping systems; planning, management alternatives were proposed and use of water in the watershed, and the methodological guide . Inventory results and the best options for water management in the watershed and the use of crop systems were spread out. The research was carried out in a cooperative way , which involved leaders, directors and partners of water systems. Drinking water and community irrigation contributed and helped in providing primary information . Also, the secondary data were organized, validated and systematized, and observations interviews, workshops, meetings, and field tests were spread out. Among the achieved results are the establishment of the Parish Water Forum and a methodological guide to carry out inventory water ; an area of 13, 378 ha was determined to reforest in the watershed, it was established that the organization of drinking water systems and community irrigation are not good; water quality in the biological sense is between good and bad (due to total coliforms are greater than 79 UFC ), and it was found that there was a deficit of water in the watershed in the months May to November, with the most critical month of August, because the Chantaco river (at the close of the watershed) has a flow rate of 264, 7 l / s, so it has a deficit of 4 360, 878.9 m³. Another achieved result was to determine five options for the management and water protection in the watershed: a) Plant or regenerate native plants, b) Maintain at least three meters in each of the stream bank, c) restore or build ponds (earthworks) in the high parts of the Trapa mountain and Guayrapamba , d) reforest areas of dense humid forest, high wet shrub, high dry shrub and high barren plateau, and e ) Reconstruct and build stone pyramids, around the slopes that are located in a grassland area. Also, the technical elements for water management in horticulture cultivation, with spray irrigation, agronomic data such as crop, soil hydro constants, weather and soil data and terrain features, among others, were established. The proposal integrated water management in the Chuquiribamba-Chantaco water shed was established. In this, the creation of the Committee to Support Water Management of the watershed is considered, which will be integrated by the actors involved in water management: Parish Water Forum, the association of drinking water and community irrigation, a representative of the Parish Councils, a representative of the Municipality of Loja, a representative of the Irrigation Company and Production Loja Provincial Government, a representative of SENAGUA, MAGAP and Ministry of Environment. This Committee will lead the implementation of the 22 specific projects contained in the Proposal: Integrated Water Management in the micro-Chantaco Chuquiribamba, based on vision, mission and strategic objectives proposed. To have a Methodological Guide of Water Inventory is essential to determine the quantity and quality of water and set the technical functionality and social systems drinking water and irrigation in the watershed community study. The changing practices of farmers, of the study area, has a detrimental impact on watershed management. The positive is that most producers are watering their horticulture crops with spray irrigation . Strengthening the leadership of the Parish Water Forum is recommended in order to analyze, discuss and make decisions to implement the Proposed Integrated Water Management of the Chantaco Chuquiribamba watershed.